A peak in the critical current for quantum critical superconductors - Soon-Gil Jung (Nature Portfolio, 2018)
Knowledge of critical current may provide important information to understand unconventional superconductivity and quantum critical behavior. Here, Jung et al. observe a peak in the pressure dependence of the zero-field critical current at a hidden quantum critical point in pure and Sn-doped heavy fermion superconductor CeRhIn5.